An atmospheric water harvester with fast and energy‐saving water removal and recovery. Issue 1 (15th February 2023) - Song, Jiayu; Liu, Zhang; Boñgol, Jhoanne Pedres; Zhang, Zhaoxin; Yeung, King Lun
Abstract: Moisture removal and water recovery from the air are vital for regulating indoor humidity and mitigating water scarcity. Most atmospheric water harvesters (AWH) focus primarily on increasing the moisture capture rate, but for it to be economical and sustainable, it is essential to consider the energy required to recover and harvest the captured water. Here, a mechanically flexible, biphilic sorption‐based AWH made of green, environmentally friendly material is presented. It consists of a hygroscopic chitosan polymer embedded within a flexible, hydrophobic silica xerogel that can harvest 86.3 g water/g chitosan at 97% relative humidity and 25°C reaching saturation after 30 days (i.e. 2.88 g water/g chitosan/day). Roughly 88% of the sorbed moisture was recovered by mechanical squeezing (ca. 0.020 MPa) within 150 s. Repeated water harvesting experiments and uniaxial compression tests demonstrate that chitosan‐silica xerogel is durable for long‐term operations, providing a fast, reliable, and sustainable moisture removal and water harvesting tool.